Redox-dependent conformational changes of a proximal [4Fe-4S] cluster in Hyb-type [NiFe]-hydrogenase to protect the active site from O2 - Muhd Noor, Noor Dina; Matsuura, Hiroaki; Nishikawa, Koji; Tai, Hulin; Hirota, Shun; Kim, Jaehyun; Kang, Jiyoung; Tateno, Masaru; Yoon, Ki-Seok; Ogo, Seiji; Kubota, Shintaro; Shomura, Yasuhito; et al. (Royal Society of Chemistry, 2018)
Citrobacter sp. S-77 [NiFe]-hydrogenase harbors a standard [4Fe–4S] cluster proximal to the Ni–Fe active site. The presence of relocatable water molecules and a flexible aspartate enables the [4Fe–4S] to display redox-dependent conformational changes. These structural features are proposed to be the key aspects that protect the active site from O2 attack.